Evaluation of the DREAM Technique for a High-Throughput Deorphanization of Chemosensory Receptors in Drosophila - Koerte, Sarah; Keesey, Ian W.; Khallaf, Mohammed A.; Cortés Llorca, Lucas; Grosse-Wilde, Ewald; Hansson, Bill S.; Knaden, Markus (Frontiers in Molecular Neuroscience, 2018)
In the vinegar fly Drosophila melanogaster, the majority of olfactory receptors mediating the detection of volatile chemicals found in their natural habitat have been functionally characterized (deorphanized) in vivo. In this process receptors have been assigned ligands leading to either excitation or inhibition in the olfactory sensory neuron (OSN) where they are expressed. In other, non-drosophilid insect species, scientists have not yet been able to compile datasets about ligand-receptor interactions anywhere near as extensive as in the model organism D. melanogaster, as genetic tools necessary for receptor deorphanization are still missing. Recently it was discovered that exposure to artificially high concentrations of odorants leads to reliable alterations in mRNA levels of interacting odorant receptors in mammals. Analyzing receptor expression after odorant exposure can, therefore, help to identify ligand-receptor interactions in vivo without the need for other genetic tools. Transfer of the same methodology from mice to a small number of receptors in D. melanogaster resulted in a similar trend, indicating that odorant exposure induced alterations in mRNA levels are generally applicable for deorphanization of interacting chemosensory receptors. Here we evaluated the potential of the DREAM (Deorphanization of receptors based on expression alterations in mRNA levels) technique for high-throughput deorphanization of chemosensory receptors in insect species using D. melanogaster as a model. We confirmed that in some cases the exposure of a chemosensory receptor to high concentration of its best ligand leads to measureable alterations in mRNA levels. However, unlike in mammals, we found several cases where either confirmed ligands did not induce alterations in mRNA levels of the corresponding chemosensory receptors, or where gene transcript-levels was altered even though there is no evidence for a ligand-receptors interaction. Hence, there are severe limitations to the suitability of the DREAM technique for deorphanization as a general tool to characterize olfactory receptors in insects.